THE POTENTIAL OF SOCIAL MEDIA AS A TOOL FOR AUTHENTIC LANGUAGE LEARNING - Hafizov A. A. (Bright Mind Publishing, 2025)
In the digital era, social media has emerged as a powerful tool for language acquisition. This process is facilitated by authentic content, interactive engagement formats, and opportunities for real-time communication with native speakers. This article explores the key mechanisms through which social media can enhance language learning, analyzes existing research on the topic, and provides recommendations for the effective integration of this approach into educational practices.
Keywords: Social media, language learning, digital technology, authentic content, communicative practice.